Digital games as history - Chapman, Adam, 1984-, author.
1 online resource (xii, 290 pages)
Keywords: "This book provides the first in-depth exploration of video games as history. Chapman puts forth five basic categories of analysis for understanding historical video games: simulation and epistemology, time, space, narrative, and affordance. Through these methods of analysis he explores what these games uniquely offer as a new form of history and how they produce representations of the past. By taking an inter-disciplinary and accessible approach, the book provides a specific and firm first foundation upon which to build further examination of the potential of video games as a historical form"--From publisher's website.